2013
DOI: 10.1002/ejlt.201200434
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and polymorphic behavior of shea stearin and the effect of removal of polar components

Abstract: The crystallization of shea stearin was investigated both before and after pre‐treatment with silica to remove a small amount (0.7 wt%) of diacylglycerols (DAGs) and oxidized material. NMR (for solid fat content), X‐ray diffraction (XRD), polarized light microscopy, confocal Raman microscopy, and non‐isothermal, isothermal and “stop‐and‐return” differential scanning calorimetry (DSC) techniques were used. Four major polymorphs previously found with 1,3‐distearoyl‐2‐oleoyl‐sn‐glycerol (StOSt) were detected: α, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…Such diunsaturated and triunsaturated triacylglycerols might be ideal sources for producing cooking oils, frying fats and other structured lipids by further blending or interesterification [17,18]. Furthermore, relatively high content of diacylglycerol in MKF (2.7-5.8%) would give chocolate its undesirable physical properties [1,5,19]. As reported in SOS-rich fats or CB systems, the presence of diacylglycerol delayed the transition of Hm-SMT into a more stable polymorph, resulting in difficulties in the tempering of the fat [2,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such diunsaturated and triunsaturated triacylglycerols might be ideal sources for producing cooking oils, frying fats and other structured lipids by further blending or interesterification [17,18]. Furthermore, relatively high content of diacylglycerol in MKF (2.7-5.8%) would give chocolate its undesirable physical properties [1,5,19]. As reported in SOS-rich fats or CB systems, the presence of diacylglycerol delayed the transition of Hm-SMT into a more stable polymorph, resulting in difficulties in the tempering of the fat [2,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, relatively high content of diacylglycerol in MKF (2.7-5.8%) would give chocolate its undesirable physical properties [1,5,19]. As reported in SOS-rich fats or CB systems, the presence of diacylglycerol delayed the transition of Hm-SMT into a more stable polymorph, resulting in difficulties in the tempering of the fat [2,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This was then placed on the microscope in a temperature-controlled cabinet to investigate the microstructure of the fat after crystallization (1 h). [21] Data obtained from the study clearly shows that the content and composition of fatty acids found in the ASO and SNO are different. The results show that ASO contains stearic and oleic acid with a small percentage (less than 1%) representing palmitic acid and arachidic acid.…”
Section: Microscopy Analysismentioning
confidence: 88%
“…The presence of oleic and linoleic acids in the SNO accounts for its high level of unsaturated fatty acids. [22] Ray et al reported the presence of 1-stearoyl-3-oleoyl-glycerol and 1-stearoyl-2-oleayl-glycerol DAGs in shea stearin, [21] therefore the broadening of peaks may be attributed to the inhibitory effect on crystallization/ recrystallization of DAGs present in the SNO. The fatty acid composition of ASO and SNO were comparable to their iodine values of 36.86 (mg I 2 100 g À1 ) and 52.06 (mg I 2 100 g À1 ), respectively.…”
Section: Microscopy Analysismentioning
confidence: 99%
“…As for the polymorphic transition, the presence of minor components can have one or more of these effects: (a) stabilization of unstable polymorphs; (b) destabilization of stable polymorphs and (c) increase in the energy barrier for transformation (slowing down the transformation) [10 ,11,23]. Interestingly, recent studies on silicon treated shea stearin showed that the slowing down effect of DAGs was limited only to lower polymorphs while, the transformation to higher polymorphs was unaffected [23]. Acevedo and Marangoni recently demonstrated that it is possible to functionalize blends of fully hydrogenated oil and liquid oil by using specific emulsifiers under controlled crystallization conditions.…”
Section: Influence Of Minor Lipid Components On Fat Crystallizationmentioning
confidence: 99%